A Review Gender diversity dan Environmental, Social, and Governance (ESG) terhadap financial performance - Agustin, Maulina; Deliana, Marlina (Talenta Publisher, 2023)
The purpose of conducting research is to see the relationship between gender diversity (in the form of female leadership) on financial performance, the influence of environmental, social, and governance (ESG) on financial performance, as well as the effect of gender diversity on financial performance through environmental, social, and governance (ESG). . Stakeholder theory argues that companies should be accountable not only to their stakeholders (such as customers or employees), but also to their secondary stakeholders (such as social communities, local authorities, subcontractors, suppliers, non-governmental organizations. This research is a literature review which was carried out from various journal sources. The research results from the literature review conducted, show that there is a 75% link between gender diversity, ESG and the company's financial performance.